Tangping (Lying Flat): Subjectivation, Lifestyles, and Voice among Young Chinese - Rocca, Jean-Louis (Sociétés politiques comparées. Revue européenne d’analyse des sociétés politiques, 2025)
Since the 2010s, new cultural phenomena have emerged in China among the young generation of people born during the “Chinese Miracle”, all challenging the norms and values that the previous generation helped to create. The most interesting of these is Tangping (lying flat), a buzzword that was generated online. It expresses a desire to escape the hyper-competitive culture that has become established in both education and the workplace, as well as the “responsibility ideology” which encourages people to work hard, marry, have babies, and consume. It is not only middle-class young people are who are lying flat. All social categories are affected, but the way in which it is practised varies depending on people’s social status. There are many ways to participate in the phenomenon, ranging from a complete change of life to a simple sign of distinction, and many “Tangpingists” only aspire to have a temporary “rest” from this exhausting society. Tangping has no organisation and no leaders. However, it poses a challenge to the Chinese Dream – the goal of building a prosperous society and making China a powerful country. Tangping (Restons couché(e)s) : subjectivation, styles de vie et opinions parmi la jeunesse chinoise Depuis les années 2010, de nouveaux phénomènes culturels ont émergé en Chine parmi la jeune génération née pendant le « miracle chinois », remettant tous en question les normes et les valeurs que la génération précédente avait contribué à créer. Le plus intéressant d’entre eux est Tangping (restons couché(e)s), un terme né sur Internet et qui est devenu viral. Il exprime le désir d’échapper à la culture hypercompétitive qui s’est imposée tant dans l’éducation que dans le monde du travail, ainsi qu’à l’« idéologie de la responsabilité » qui encourage les gens à travailler dur, à se marier, à avoir des enfants et à consommer. Les jeunes de la classe moyenne ne sont pas les seuls à « tangping ». Toutes les catégories sociales sont concernées, mais la manière dont il est pratiqué varie en fonction du statut social. Il existe de nombreuses façons de participer à ce phénomène, allant d’un changement complet de vie à un simple signe de distinction, et de nombreux « tangpingistes » aspirent seulement à un « repos » temporaire loin de cette société épuisante. Le Tangping n’a pas d’organisation ni de leaders. Cependant, il représente un défi pour le « Rêve chinois », qui consiste à construire une société prospère et à faire de la Chine un pays puissant.